2015
DOI: 10.1038/nature14878
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐genome sequencing identifies EN1 as a determinant of bone density and fracture

Abstract: SUMMARY The extent to which low-frequency (minor allele frequency [MAF] between 1–5%) and rare (MAF ≤ 1%) variants contribute to complex traits and disease in the general population is largely unknown. Bone mineral density (BMD) is highly heritable, is a major predictor of osteoporotic fractures and has been previously associated with common genetic variants1–8, and rare, population-specific, coding variants9. Here we identify novel non-coding genetic variants with large effects on BMD (ntotal = 53,236) and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
576
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 507 publications
(610 citation statements)
references
References 40 publications
12
576
4
2
Order By: Relevance
“…Participating studies separately genotyped samples and imputed them to WGS-based reference panels. The most recent imputation panels, such as the UK10K and 1000 Genomes Project (v.3) combined panel (7,562 haplotypes from the UK10K project and 2,184 haplotypes from the 1000 Genomes Project 9 ) and the Haplotype Reference Consortium (HRC) panel (64,976 haplotypes 15 ), enabled more accurate imputation of low-frequency variants than the UK10K or 1000 Genomes reference panel alone. 9 Specifically, 11 of the 17 participating cohorts were imputed to the combined UK10K and 1000 Genomes reference panel (total number of imputed individuals included in the meta-analysis ¼ 25,589).…”
Section: Wgs Genotyping and Imputationmentioning
confidence: 99%
See 1 more Smart Citation
“…Participating studies separately genotyped samples and imputed them to WGS-based reference panels. The most recent imputation panels, such as the UK10K and 1000 Genomes Project (v.3) combined panel (7,562 haplotypes from the UK10K project and 2,184 haplotypes from the 1000 Genomes Project 9 ) and the Haplotype Reference Consortium (HRC) panel (64,976 haplotypes 15 ), enabled more accurate imputation of low-frequency variants than the UK10K or 1000 Genomes reference panel alone. 9 Specifically, 11 of the 17 participating cohorts were imputed to the combined UK10K and 1000 Genomes reference panel (total number of imputed individuals included in the meta-analysis ¼ 25,589).…”
Section: Wgs Genotyping and Imputationmentioning
confidence: 99%
“…WGS for the ALSPAC and TUK cohorts has been described in detail in a previous publication from our group. 7 Table S8 summarizes the data-generation method for sequencing-based cohorts. Participating studies separately genotyped samples and imputed them to WGS-based reference panels.…”
Section: Wgs Genotyping and Imputationmentioning
confidence: 99%
“…Using this approach, the novel candidate gene EN1 was identified, significantly related to both BMD and fracture risk. Animal models and in vitro studies indicate a possible role for EN1 in osteoblasts, offering an exciting opportunity for the discovery of new mechanisms in bone formation (53). Finally, this study also suggests that lower frequency variants may have higher impact on BMD and fractures, warranting further studies.…”
Section: Candidate Genes Identified Through Genome-wide Association Smentioning
confidence: 99%
“…In 2015, a breakthrough GWAS based on wholegenome sequencing was published by Zheng and cols., with enough power to detect the effects of lowfrequency variants (minor allele frequency [MAF] between 1-5%), which are usually not contemplated by genotype-based GWAS (53). Using this approach, the novel candidate gene EN1 was identified, significantly related to both BMD and fracture risk.…”
Section: Candidate Genes Identified Through Genome-wide Association Smentioning
confidence: 99%
“…DXA-based studies have led the way in identifying genetic influences on the skeleton, exemplified by a recent genome wide association study (GWAS) followed by replication which identified allelic variation at the EN1 locus as a novel, but low frequency determinant of bone mineral density (BMD) and fracture risk (1) . One of the main advantages of DXA scans is that due to their wide availability and low radiation dose, large scale GWAS meta-analyses involving many thousands of individuals are possible, providing the requisite power for studies of this type.…”
Section: Introductionmentioning
confidence: 99%